Case Report: Liver Transplantation in Homozygous Familial Hypercholesterolemia (HoFH)—Long-Term Follow-Up of a Patient and Literature Review - Mlinaric, Matej; Bratanic, Nevenka; Dragos, Vlasta; Skarlovnik, Ajda; Cevc, Matija; Battelino, Tadej; Groselj, Urh (Frontiers in Pediatrics, 2020)
Homozygous familial hypercholesterolemia (HoFH) is a rare inherited metabolic disorder, frequently leading to an early cardiovascular death if not adequately treated. Since standard medications usually fail to reduce LDL-cholesterol (LDL-C) levels satisfactorily, LDL-apheresis is a mainstay of managing HoFH patients but, at the same time, very burdensome and sub-optimally effective. Liver transplantation (LT) has been previously shown to be a promising alternative. We report on a 14-year-long follow-up after LT in a HoFH patient.. At the age of four, the patient was referred to our institution because of the gradually increasing number of xanthomas on the knees, elbows, buttocks, and later the homozygous mutation c.1754T>C (p.Ile585Thr) on the LDL-receptor gene was confirmed. Despite subsequent intensive treatment with the combination of diet, statins, bile acid sequestrant, probucol, and LDL-apheresis, the patient developed valvular aortic stenosis and aortic regurgitation by 12 years. At 16 years, the patient successfully underwent deceased-donor orthotopic LT. Nine years post-LT, we found total regression of the cutaneous xanthomas and atherosclerotic plaques, and with normal endothelial function. Fourteen years post-LT, his clinical condition remained stable, but LDL-C levels have progressively risen. Also, a systematic review of the literature and guidelines on the LT for HoFH patients was performed. Six of the 17 identified guidelines did not take LT as a treatment option in consideration at all. But still the majority of guidelines suggest LT as an exceptional therapeutic option or as the last resort option when all the other treatment options are inadequate or not tolerated. Most of observed patients had some kind of Cardiovascular disease before the LT. In 76 % of LT the cardiovascular burden did not progress after LT. Most of the follow-up data were short-termed, only a few case reports have followed patients for ten or more years after LT. LT is a feasible therapeutic option for HoFH patients, reversing atherosclerotic changes uncontrollable by conservative therapy, thus importantly improving the HoFH patient’s prognosis and quality of life. LDL-C levels might be increasing over time post-LT.